Optimization method of wireless indoor coverage based on big data analysis - Yuanfeng GONG; Yi HUANG (Dianxin kexue)
The indoor prediction method of indoor depth coverage includes user complaints,CQT and propagation model correction,and the prediction error of these methods is large.Firstly,the indoor coverage optimization method was introduced.Then,the indoor deep coverage optimization method based on big data was introduced,which significantly improved the network quality and user perception.Finally,the application case was introduced,which provided a very important reference and guiding significance for the construction,optimization and maintenance of indoor deep coverage in the later period.